2017
DOI: 10.1155/2017/4820935
|View full text |Cite
|
Sign up to set email alerts
|

Machine-Learning Classifier for Patients with Major Depressive Disorder: Multifeature Approach Based on a High-Order Minimum Spanning Tree Functional Brain Network

Abstract: High-order functional connectivity networks are rich in time information that can reflect dynamic changes in functional connectivity between brain regions. Accordingly, such networks are widely used to classify brain diseases. However, traditional methods for processing high-order functional connectivity networks generally include the clustering method, which reduces data dimensionality. As a result, such networks cannot be effectively interpreted in the context of neurology. Additionally, due to the large sca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
18
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 59 publications
(58 reference statements)
0
18
0
Order By: Relevance
“…Nearly half of the models (48.3% [268 of 555]) were found in studies authored by those with academic training in computers and data science (eTable 2 in Supplement 1). Schizophrenia (25.4% [141 of 555 models])…”
Section: Resultsmentioning
confidence: 99%
“…Nearly half of the models (48.3% [268 of 555]) were found in studies authored by those with academic training in computers and data science (eTable 2 in Supplement 1). Schizophrenia (25.4% [141 of 555 models])…”
Section: Resultsmentioning
confidence: 99%
“…Another research avenue could also be the inclusion of neuroimaging biomarkers, which have been identified for PTSD. [57][58][59][60][61] Indeed, the combination of self-reported data and neuroimaging features could provide a complete model of the risk of depressive status in military personnel. A study revealed that using functional MRI data in an SVM could identify patients with severe depression, but did not perform well for milder depression.…”
Section: Discussionmentioning
confidence: 99%
“…Hilbert et al [107] used SVM on generalized anxiety disorder (GAD), MDD, and HC subjects as a case classification and to distinguish GAD from MD as a disorder classification. Guo et al [108] proposed a new method for generating a high-order minimum spanning tree function to connect the network. In addition, they applied multi-kernel SVM to the selected features to obtain classification results.…”
Section: Major Depressive Disordermentioning
confidence: 99%